The Influence of Gender, Age, and Education Diversity on the Board of Directors on Company Performance - M. Wahyu Ramzy Ramadhan; Riris Rotua Sitorus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to examine the influence of board diversity, measured in terms of gender, education, and age, on company performance. The study utilizes panel data, with a total sample of 1,080 companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2021. The findings indicate that board diversity in terms of gender and education significantly and positively affects company performance, as measured by Return on Assets (ROA). However, directors' age diversity does not significantly impact company performance. Based on the coefficient of determination, the diversity variables in this study can only explain 3.86% of the variation in company performance, while the remaining 96.14% is attributed to other variables not included in this research model. Therefore, it is recommended to consider these research findings as a foundation, but also to consider each company's unique context and characteristics.